MEASURING THE GAP IN EMPLOYABILITY SKILLS AMONG MALAYSIAN GRADUATES - Janitha Nadarajah (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This research relates to the issue of unemployment among the local graduates and lack of employability skills. The objective of this research is to measure the employability skills among graduates from higher education institutions in Malaysia. The research identifies the gap in employability among the graduates and the competencies needed in the job market. 300 graduates from higher education institutions in Malaysia participated in this research. The findings of this research revealed that the graduates are equipped with most of the generic employability skills such as ICT skills, teamwork, leadership skills, and good time management. However, the graduates would still need to improve their communication, problem-solving and analytical skills. The research also found a mismatch in the employability skills between the graduates and job market requirements.